Professional well-being : enhancing wellness among psychiatrists, psychologists, and mental health clinicians - Gengoux, Grace W. (American Psychiatric Association Publishing, 2020)
"This volume is a collaboration by several psychiatrists and psychologists who posit a new culture, one that is supportive of the health and well-being of health care professionals and the patients and populations they serve. The individual and systemic barriers to professional well-being and the unique challenges faced by health care providers at different stages of professional and personal development are examined. Personal resilience and realistic strategies to improve well-being are discussed. Detailed case studies and vignettes and thought-provoking discussion questions and exercises are included"--